URGENSI KOMUNIKASI PENDIDIKAN ISLAM DALAM MEMBANGUN PENDIDIKAN HARMONI PASCA KONFLIK MASYARAKAT - Hamlan Andi Baso Malla (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2014)
Social conflict that has occurred in the District of Sigi cannot be separated from the withering of social values that have become the foundation of society so far in the same group, culture, ethnic group, religion, and social values. This similarity does not guarantee that people can live in peace and harmony. Therefore, communication is needed to spread Islamic values to community in order that social conflict between people of villages in Sigi can be avoided. This in turn can lead to building peace and social integration based on Islamic values.